Livestock production and foodborne diseases from food animals in Thailand - Padungtod P. (2014)
Thailand is a developing nation dependent on agriculture. Due to lack of modern public health practices, she suffers from the consequences of foodborne illnesses. The number of foodborne infection cases has nearly doubled in the past 10 years. Salmonella and Campylobacter pose the greatest risk of bacterial contaminants, mostly from pigs and chickens, and this paper will review livestock production systems and foodborne diseases from cases stemming from these sources. Due to the complexity of the livestock production systems, collection of data to date has been sporadic, but it is clear that controls are needed in slaughterhouse processing methods, and more communication between agencies and surrounding regions is paramount for proper surveillance to have any significant effect.